2012
DOI: 10.1364/ao.51.002485
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional Dammann vortex array with tunable topological charge

Abstract: We describe a kind of true 3D array of focused vortices with tunable topological charge, called the 3D Dammann vortex array. This 3D Dammann vortex array is arranged into the structure of a true 3D lattice in the focal region of a focusing objective, and these focused vortices are located at each node of the 3D lattice. A scheme based on a Dammann vortex grating (DVG) and a mirror is proposed to provide a choice for changing the topological charge of the 3D Dammann vortex array. For experimental demonstration,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 24 publications
0
22
0
Order By: Relevance
“…Those vortices of the dipole array are located in several coaxial planes along the optical axis, and thus this vortex array enables one to freely manipulate the focused vortex on a certain cross-sectional plane by changing topological charge of the incident beam. Moreover, similar to a 3D monopole vortex array, we will demonstrate that it is also possible to achieve a 3D dipole vortex array when the SDZP is employed to replace the DZP in a focusing system of 3D Dammann vortex array described in [11].…”
Section: Introductionmentioning
confidence: 87%
See 3 more Smart Citations
“…Those vortices of the dipole array are located in several coaxial planes along the optical axis, and thus this vortex array enables one to freely manipulate the focused vortex on a certain cross-sectional plane by changing topological charge of the incident beam. Moreover, similar to a 3D monopole vortex array, we will demonstrate that it is also possible to achieve a 3D dipole vortex array when the SDZP is employed to replace the DZP in a focusing system of 3D Dammann vortex array described in [11].…”
Section: Introductionmentioning
confidence: 87%
“…In our previous paper [11], we showed that a 3D monopole vortex array can be achieved by introducing a vortex beam as the incident field of the focusing system of a 3D Dammann array that is mainly based on a DZP and a conventional two-dimensional (2D) DG. Here we use the 1 × 5 SDZP designed above to replace the DZP in the focusing system of the 3D Dammann vortex array and all other parts of the system are the same as the experimental setup shown in Fig.…”
Section: Generation Of 3d Dipole Vortex Arraysmentioning
confidence: 99%
See 2 more Smart Citations
“…Dammann gratings structures have also been employed to produce sets of parallel vortex patterns [12,13]. In [14] the authors describe a setup based on a Dammann vortex grating to generate a 3D array of focused vortices with tunable topological charge. The phase modulation of an annular aperture array has also been proposed [15] to create distributions of high-order vortex cones.…”
Section: Introductionmentioning
confidence: 99%